The Association Between Market Determined and Accounting Determined Risk Measures. - Beaver, William; Kettler, Paul; Scholes, Myron (The Accounting Review, 1970)
The article examines the relationship between the accounting determined and market determined measures of risk. Previous research would suggest that financial statement ratios can be used as measures of default risk, but little is known of their association with the concept of risk as defined in portfolio theory. The variance of a portfolio's return is the sum of two terms. Empirically, there may be positive association between a security's variance and its average covariance with other securities. In sum, portfolio theory provides a measure of security risk that has both a priori and empirical support. In particular, the accounting risk measures can be viewed as surrogates for the total variability of return of a firm's common equity securities. Computing an average of the payout ratios over several years does not adequately deal with this problem, because one extreme year will still dominate the average. Accounting data provided superior forecasts of the market determined risk measure for the time periods studied. In summary, this study will provide some additional insight into the interaction between accounting data and market price variables and will help to provide a foundation for structuring the accounting system in a way that will facilitate decisions by investors.